Tiktok and the Deviation of Student Behavior in the Perspective of Ahmad Baradja's Thought - Laily Nur Arifa (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2023)
Tiktok is a widely-used application in Indonesia; its users reach 22.2 million at present. Some problems have arisen due to FYP-purpose, including dancing in public, actions that lead to immorality, and many other inappropriate behaviors against Islam and decency values in Indonesia. This study used qualitative research using a content analysis design. The number of accounts being studied was 105, with 7730 videos. The study results are: first, the Tiktok content typology of UIN Malang students is: daily activity (5,2%); TikTok hits 21,28571; a day in the life of 2,6 %; telling stories, 2,05%; hashtag challenges, 4,03%; dance challenges, 17.9 %; life at 11,98%; frivolous, 27,74%; education, 2,98%; others, 4,28%. Secondly, dominant behaviours of UIN students in their TikTok content include narcissism by making close-up videos, dancing to music, imitating viral sounds, aggressive behaviours in answering QnA, laughing at other people or an event considered funny, interacting with different gender, sharing sessions, calm and direct behavior, exposing body parts forbidden according to Islam, posing in specific styles, talking about other people, and flexing. Third, according of Ahmad Baradja Islamic behavior analysis, accounts with content against Islam are 31%, while those with content not against Islam are 69%. Most violations involve exposing body parts forbidden in Islam, interaction with different gender, the absence of shame, riya’ (pretending virtuousness) and expressing bad words.An interesting finding reveals that none of the first three contents has violated Islamic rule. Only in the fourth content did that violation start to appear. This violation then occurred multiple times in the following contents.